Activity estimation and biokinetic analysis of 99mTc-DMSA in renal infant patients using a gamma camera. (August 2018) - Teles, P.; Costa, J.; Costa, D.; Matela, N.; Vaz, P.
Highlights: In vivo activity data in infants obtained with a gamma camera. Activities estimated via an adapted methodology from MIRD pamphlet No. 16. Obtained excretion, retention and absorption times compared with adult values. Sheds light on the biokinetics and dosimetry of infant patients. Abstract: Biokinetic data from the administration of radiopharmaceuticals is essential in nuclear medicine dosimetry. It has particular significance in children, as their metabolism is very different from adults. Biokinetic models for paediatric patients could therefore need to be adapted to better reflect their absorption, retention and excretion functions, when compared to adults. Obtaining quality in vivo infant or paediatric biokinetic data is then essential to improve the available reference models, which in turn can lead to the optimization of paediatric procedures and protocols in clinical practice. This study analyses the biokinetic behaviour of 99m Tc-dimercaptosuccinic acid (DMSA), in 8 infants aged 4 months to 2 years old, through an imaging study using a gamma camera, and compares the obtained values with those obtained with the reference ICRP biokinetic model. The in vivo data was treated using an adapted methodology from the MIRD 16 pamphlet. Activity curves for the liver, the kidney and the whole body, were built, and new effective absorption, retention and excretion half-lives were estimated, and compared with the reference biokinetic parameters of ICRP 128. The obtained residence time in the kidneys of 2.56 h, has a deviation of 30.8% to the ICRP 128 value of 3.70 h. The obtained maximum uptake in the kidneys was of 0.22/A0, which compares to the value of 0.31/A0 for ICRP. The obtained biokinetic parameters were used to estimate the absorbed dose. The obtained dose values are smaller than the reference ICRP 128 ones by 32.1% in the kidneys, and 18.4% in the liver.